Interaksi di Kelas Perspektif Pendekatan Konstruktivistik Untuk Pengembangan Akhlak - Hanun Asrohah (Universitas Islam Negeri Mataram, 2014)
Morality and human behavior are created as social construction, and developed through education. This article is aimed at explaining about interactions amongst students in the classroom, based on constructivist learning theory, as source of positive atmospheres that are very important for the formation of character and morality. Morality is not simply taught or absorbed in subjects like civics or social studies. It must be developed in a variety of activities in the classroom. According to the theory, developing a good and appropriate atmosphere is necessary to introduce good values and norms in which students learn to construct their own knowledge through continuous interactions with social contexts, and develop their ideas and feelings about people and objects. They can learn about life critically and understand how people live and under what condition they live, whether in peace or violence, with affection or hostility, cooperation or fights, and satisfaction or disappointment.